Vitality Forms Expressed by Others Modulate Our Own Motor Response: A Kinematic Study - Di Cesare, Giuseppe; De Stefani, Elisa; Gentilucci, Maurizio; De Marco, Doriana (Frontiers in Human Neuroscience, 2017)
During social interaction, actions and words may be expressed in different ways, for example, gently or rudely. A handshake can be gentle or vigorous and, similarly, tone of voice can be pleasant or rude. These aspects of social communication have been named vitality forms by Daniel Stern. Vitality forms represent how an action is performed and characterize all human interactions. In spite of their importance in social life, to date it is not clear whether the vitality forms expressed by the agent can influence the execution of a subsequent action performed by the receiver. To shed light on this matter, in the present study we carried out a kinematic study aiming to assess whether and how visual and auditory properties of vitality forms expressed by others influenced the motor response of participants. In particular, participants were presented with video-clips showing a male and a female actor performing a “giving request” (give me) or a “taking request” (take it) in visual, auditory, and mixed modalities (visual and auditory). Most importantly, requests were expressed with rude or gentle vitality forms. After the actor’s request, participants performed a subsequent action. Results showed that vitality forms expressed by the actors influenced the kinematic parameters of the participants’ actions regardless to the modality by which they are conveyed.